The Implementation Of Information Technology In The Development Of Left And Right Brain At An Early Age In The World Of Education - Wahyu Azhar Ritonga; Eriani; Ismi Yulizar; Uswatun Hasanah Masra Tangse; Yuli Yani; Dwina Putri (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of the study is to develop the use of the right and left brain in early childhood through the implementation of information technology in this case learning using video with words. Education in learning that is done must keep up with the times by utilizing information technology we often mention with the era of revolution 4.0. Research methods use descriptive qualitative methods by means of observation and interview of teachers, Then the data obtained in the test using spss for windows with a population of 60 early childhood results obtained Fcount = 23,347 > Ftable = 3.16 so it can be said that the implementation of information technology in learning in the form of video display is very good in the development of the right and left brain in each individual early childhood.